Implementasi Model Pembelajaran Cooperatif Learning Dengan Media Konkret Untuk Meningkatkan Hasil Belajar Pembagian Bilangan Asli Dalam Muatan Pelajaran Matematika Siswa kelas II SD Negeri 4 Padangkerta - Ni Made Ariyanti (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study discusses the low mathematics learning outcomes of Class II of SD Negeri 4 Padangkerta. This type of research is Classroom Action Research. The place of action is in SD Negeri 4 Padangkerta. Wendra (2009: 53) states that "the subject of research is the person subject to action". In other words, the subject is where the research data is obtained. This research was carried out in SD Negeri 4 Padangkerta in the odd semester, completed in class II with 27 students consisting of 9 female and 18 male students. The object that reflects the process in this study is the Cooverative Learning model with concrete media in the content of mathematics lessons. Meanwhile, the object that reflects the product is the concept of division of original student numbers in mathematics. This data collection uses a collection method to measure student learning activities and a test method to measure student learning outcomes. After the data is collected, it is then analyzed using descriptive statistical methods. Based on the results of the research and discussion in the previous chapter, it can be concluded that through the implementation of cooperative learning models with concrete media can improve the understanding of the concept of number distribution for grade II students at SD Negeri 4 Padangkerta. The success of the implementation of the cooverative learning model with concrete media is also evidenced by the average value of understanding results at the end of the first cycle that is 74.81 and the average value of understanding the concepts that support at the end of the second cycle is 86.91. Based on the graph above, the average value of the concept understanding results from cycle I to cycle II increases the increase by 12.1. The percentage of students who reached KBM from cycle I to cycle II also increased by 25.92%, from 66.67% to 92.59%.